2021
DOI: 10.3389/fneur.2021.694970
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcomes in Disorders of Consciousness Following Transcranial Magnetic Stimulation: A Systematic Review and Meta-Analysis of Individual Patient Data

Abstract: Background: There are few treatments with limited efficacy for patients with disorders of consciousness (DoC), such as minimally conscious and persistent vegetative state (MCS and PVS).Objective: In this meta-analysis of individual patient data (IPD), we examine studies utilizing transcranial magnetic stimulation (TMS) as a treatment in DoC to determine patient and protocol-specific factors associated with improved outcomes.Methods: We conducted a systematic review of PubMed, Ovid Medline, and Clinicaltrials.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
2
22
0
1
Order By: Relevance
“…The crossover design has the advantage of eliminating individual subject differences from the overall treatment effect and is suitable for chronic diseases such as DoC. Therefore, this study's behavioristics and EEG results make a significant clinical observation, which helps explore the target selection of rTMS (even other NIBS treatments) for DoC and improve its clinical diagnosis and treatment ( 8 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The crossover design has the advantage of eliminating individual subject differences from the overall treatment effect and is suitable for chronic diseases such as DoC. Therefore, this study's behavioristics and EEG results make a significant clinical observation, which helps explore the target selection of rTMS (even other NIBS treatments) for DoC and improve its clinical diagnosis and treatment ( 8 ).…”
Section: Discussionmentioning
confidence: 98%
“…Currently, the available treatments for patients with DoC are limited. However, neuromodulation technology, a non-pharmacological treatment, has been successfully applied to various neurological and psychiatric conditions and holds promise for the treatment of DoC ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis, O’Neal and colleagues reported that rTMS was utilized without any adverse effects in patients with disorders of consciousness, including minimally conscious state (MCS) and vegetative state/unresponsive wakefulness syndrome [ 164 ]. Based on the individual patient data involved in their meta-analysis, O’Neal et al reported a 30.4% response rate following high-frequency rTMS at M1, with the response being defined as any change in the Coma Recovery Scale-Revised (CRS-R) score above a patient’s baseline.…”
Section: Disorders Of Consciousnessmentioning
confidence: 99%
“…Based on the individual patient data involved in their meta-analysis, O’Neal et al reported a 30.4% response rate following high-frequency rTMS at M1, with the response being defined as any change in the Coma Recovery Scale-Revised (CRS-R) score above a patient’s baseline. The more remarkable improvement in CRS-R scores was associated with MCS diagnosis, an etiology of stroke or intracranial hemorrhage, receiving 10 or more sessions of rTMS, and if the rTMS treatment was initiated within the first three months from inciting injury [ 164 ].…”
Section: Disorders Of Consciousnessmentioning
confidence: 99%